Experience Of Developing Students' RationalThinking In European Countries And PossibilitiesOf Implementation In The Education System OfUzbekistan - Toshniyazov Umirbek Khurramovich (Euro Asian Journal Publishing, 2025)
This study provides a comprehensive analysis of European experience in developing students' rational thinking and the potential for its adaptation in the Uzbek education system. The paper provides a comparative analysis of pedagogical approaches, methods, and technologies used in leading European countries to develop critical, analytical, and logical thinking. Particular attention is paid to the institutional, methodological, and cultural aspects that determine the effectiveness of European models. Based on the analysis, adapted models and practical recommendations for implementation in the Uzbek education system have been developed. The results of the study demonstrate a high potential for adapting European experience, taking into account the national and cultural characteristics of Uzbekistan
Keywords: Rational thinking; comparative pedagogy; European education system